How or not to calculate Ni(II) Werner-type complexes: evaluation of quantum chemical methods - Walther, Markus; Alzubi, Basam M.; Puchta, Ralph; Linti, Gerald W.; Meier, Roland; Van Eldik, Rudi (Journal of coordination chemistry, 2011)
Different semi-empirical methods (PM3(tm), AM1*, and PM6) that have parameters for Ni were evaluated for structural and energy calculations in comparison with DFT calculations (B3LYP/LANL2DZp) and X-ray structures. The reported crystal structure for K4[Ni(nta)2)] · 4H2O (nta = nitrilotriacetate, monoclinic space group P21/n (No. 14), a = 10.024(2) Å, b = 10.838(2) Å, c = 10.631(2) Å, β = 96.46(3)°, V = 1147.6(4) Å3, Z = 2) and the published X-ray structures for (2S,3S)-1,4-dimethoxy-2,3-bis[(salicylidene)amino]-butanenickel(II) and amine(salicylaldehyde thiosemicarbazonato)nickel(II), [Ni(AST)NH3], were used for structural evaluation. The performance of the methods was also tested for typical ligand-substitution reactions at Ni(II) centers involving displacement of NH3 by L (L = PH3, AsH3, SbH3, H2O, H2S, H2Se, H2Te) in [Ni(NH3)3NH3]2+ and [Ni(AST)NH3]. Whereas PM6 performed well for the evaluation of the structural data, AM1* was found to reproduce the energies in an excellent way.